The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1097/ta.0b013e31814699cc
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Participation of Soluble Triggering Receptor Expressed on Myeloid Cells-1 in the Systemic Inflammatory Response Syndrome After Multiple Trauma

Abstract: This is the first study providing evidence about the participation of sTREM-1 in posttraumatic SIRS. Its levels are increased and remain constant over time in patients who did not develop any complications whereas it seems to behave as an anti-inflammatory mediator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 18 publications
2
21
0
5
Order By: Relevance
“…We report that after DE exposure, mice that consumed M. tea had 2 fold or higher increases in the levels of proinflammatory/chemotactic cytokines (IL-1β and α, KC, M-CSF, RANTES, MIP-2 and MIP1-α, in the lung, as compared to mice that drank water. We also observed increases in immunosuppressive cytokines IL-6, IL-1Ra and TREM-1 (De Bie et al, 2002;Okada et al, 1995;Little and Cruikshank, 2004;Gibot and Massin, 2006;Giamarellos-Bourboulis et al, 2008).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We report that after DE exposure, mice that consumed M. tea had 2 fold or higher increases in the levels of proinflammatory/chemotactic cytokines (IL-1β and α, KC, M-CSF, RANTES, MIP-2 and MIP1-α, in the lung, as compared to mice that drank water. We also observed increases in immunosuppressive cytokines IL-6, IL-1Ra and TREM-1 (De Bie et al, 2002;Okada et al, 1995;Little and Cruikshank, 2004;Gibot and Massin, 2006;Giamarellos-Bourboulis et al, 2008).…”
Section: Discussionmentioning
confidence: 64%
“…The membrane form of TREM-1 can be cleaved into a soluble form, sTREM that is released into microenvironment (Gomez-Pina et al, 2007). While, high levels of sTREM-1 have been found in patients with severe forms of allergic asthma (Bucova et al, 2012), it has been suggested that sTREM-1 may have an antiinflammatory role, by acting through a mechanism whereby sTREM blocks interactions of membrane-bound TREM-1 with its natural ligand in a way similar to the recognized interaction between the soluble form of the TNF-α receptor and membrane TNF-α receptor (Gibot and Massin, 2006; Science Publications -Bourboulis et al, 2008). Furthermore, it has been suggested that sTREM could be used as therapeutic for inflammatory conditions such as rheumatoid arthritis and sepsis (Kim et al, 2012;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6: (1) ARDS; two studies [37,45] could not relate ARDS to IL-6 concentration alterations, whereas two other studies [48,51] found a positive correlation (Table 2); (2) Sepsis; five studies [35,41,46,47,53] found an increased IL-6 production to be predictive for the development of sepsis, whereas five other studies [28,29,38,39,55] did not (Table 3); (3) MODS; all five prospective cohort studies [3,28,34,46,51] concluded that IL-6 is markedly increased in the early development of MODS ( Dekker ABE et al . Do cytokines predict polytrauma outcome IL-10: (1) Three studies, two prospective [54,57] and one retrospective [14] , could not relate the serum IL-10 concentrations to the development of ARDS.…”
Section: Value Of Main Cytokine Concentrations For Predicting Complicmentioning
confidence: 89%
“…(1) Three studies found no relation between TNF-a and development of ARDS [37,45,51] ; (2) One study [55] concluded that concentrations were not related to development of sepsis, while one study [50] found significantly increased concentrations in septic patients; (3) Of the four studies reporting on TNF-a concentrations after trauma, two studies [31,51] found TNF-a to be related to the development of MODS, and two studies [3,57] could not relate serum concentrations [35] 2009 P-coh 1032 IL-6 10% 2…”
Section: Tnf-amentioning
confidence: 99%
See 1 more Smart Citation